Relationship between Age and Parity and the Incidence of Anemia in Third Trimester Pregnant Women: Hubungan Usia dan Paritas dengan Kejadian Anemia pada Ibu Hamil Trimester III - Tempali, Sri Restu; Astuti, Novi Dwi; Pani, Widya; Agussalim, Asrawaty; Kusika, Sri Yanti; Djamaluddin, Nevi Amriani (Poltekkes Kemenkes Palu, 2024)
Background: Anemia is a global health problem in pregnant women which can result in bleeding in the mother, while low birth weight (LBW) can occur in the fetus. Data on pregnant women with anemia at the Sangurara Community Health Center in 2023 is 23 people. Purpose: The aim was to determine the relationship between age and parity with the incidence of anemia in pregnant women in the third trimester at the Sangurara Community Health Center, Palu City. Methods: This research design uses observational analytics with a cross-sectional approach. The population in this study was 635 pregnant women and the number of samples used was 86 respondents, with a sampling technique namely Purposive Sampling. Data collection techniques use secondary data. This research was conducted at the Sangurara Health Center and carried out from 07 to 12 August 2023. Results: The results of the research showed that 23.4% of mothers of healthy age experienced anemia and 36.4% of mothers of healthy age experienced anemia. Mothers who have no parity are at risk of experiencing anemia as much as 28.2%, while mothers with parity ≥3 experience anemia as much as 25.5%. The results of the analysis obtained an age p-value of 0.237 (p > 0.05) and a parity p-value of 0.001 (p < 0.05). Conclusion: This study concludes that there is no relationship between age and the incidence of anemia in pregnant women in the third trimester and there is a relationship between parity and the incidence of anemia in pregnant women in the third trimester in the Sangurara Community Health Center area. Researchers hope to improve services and provide information so that they can reduce the incidence of anemia in pregnant women.